Irreversibility of ENSO impacts on the wintertime anomalous Western North Pacific anticyclone to CO2 forcing - Wen Zhang; Weichen Tao; Gang Huang; Kaiming Hu; Xia Qu; Hainan Gong; Kai Yang; Ya Wang (npj Climate and Atmospheric Science)
Abstract During the boreal winter, the El Niño-Southern Oscillation (ENSO) influences the East Asia-western North Pacific (WNP) climate by triggering an anomalous WNP anticyclone (WNPAC). Analysis of a suite of coupled model projections under symmetric CO2 ramp-up (RU) and ramp-down (RD) scenarios, the results reveal that WNPAC strengthens with increasing CO2 concentrations, peaks early in the CO2 RD phase, and then gradually weakens without fully returning to its initial state when CO2 concentrations restore. The irreversible recovery of WNPAC is related to enhanced negative precipitation anomalies in the tropical WNP and positive precipitation anomalies in the equatorial central and eastern Pacific. These changed precipitation anomalies are primarily driven by the climatological equatorial Pacific El Niño-like warming pattern due to various external and internal feedback processes. Our findings indicate that the irreversible change of WNPAC to CO2 forcing may hinder the winter monsoon and exacerbate climate risks in the East Asia-WNP region.